Effect of Chemical Foaming Agent in Enhancing Dispersion of Montmorillonite in Polypropylene Nanocomposite - Azguler, Ozan; Eryildiz, Meltem; Altan, Mirigul (Journal of Research Updates in Polymer Science, 2019)
Homogenous dispersion of the nano particles in the polymer matrix is a key factor in order to achieve enhanced properties of the polymer nanocomposites. Dispersion or exfoliation of nano clay is difficult in the matrix during melt mixing. In this study, dispersion of nano montmorillonite (MMT) in polypropylene (PP) was done by using chemical foaming agent during melt mixing process. Chemical foaming agent (CFA) added (1 %wt.) PP/MMT nanocomposites were prepared on twin screw extruder. Then, injection molding was done to the granulated nanocomposites in order to obtain tensile test samples. Thermal test and morphological investigations were done. Tensile test was applied to observe the difference in mechanical strength of the nanocomposites depending on the presence of the foaming agent during melt mixing process. The results have shown that, dispersion of MMT enhanced in the matrix due to addition of chemical foaming agent. This brought improved tensile strength about 19% for the PP/MMT nanocomposites within same concentrations of nano filler.